PROCUREMENT OF ULAYAT LAND FOR SUBSIDED HOUSING DEVELOPMENT IN HARAU DISTRICT LIMA PULUH KOTA REGENCY - Inggir Deviandari; Kurnia Warman; Zefrizal Nurdin (JCH (Jurnal Cendekia Hukum), 2021)
Ulayat rights are the rights that owned by a legal alliance, where the citizens of the community have the right to control the land. The Regional Regulation of West Sumatra Province, Article 2 paragraph (1) Number 6 of 2008 concerning Communal Land and Its Utilization states that the main principle of customary land is permanent based on the Minangkabau traditional philosophy “jua ndak makan bali, gadai ndak makan sando” (shall not bargaining; may not be pawned). The provisions of the regulation state that ulayat land may not be traded and may not be pawned, its ownership status may not change, except for importunate situation and condition, namely maik tabujua dalam rumah (for the death of family member), gadih gadang ndak balaki (wedding), rumah gadang katirisan (misfortune), mambangkik Batang tarandam (efforts to enforce). Land acquisition for the construction of subsidized housing is not a land acquisition according to Law Number 2 of 2012 concerning Land Procurement for Public Interest. The formulation of the problems discussed are first, the process of acquiring communal land for the construction of subsidized housing in Harau District, Lima Puluh Kota Regency, secondly the land registration process after the acquisition of customary land occurs, thirdly the legal consequences of acquiring customary land used for the construction of subsidized housing in Harau District, Lima Regency. Dozens of Cities againts customary law communities. This study uses an empirical juridical approach with the aim of finding out whether the law in the book is in accordance with the law in action. The results of the research study indicate that the process of acquiring communal land for the construction of subsidized housing is carried out by buying and selling. The construction of subsidized housing is managed by a legal entity in the form of a Limited Liability Company. The status of land ownership is just as the user of the facility that called with Hak Guna Bangunan